Newspaper collection utilization patterns in a Nigerian acedemic library (2005)
The study surveys users of the newspaper collection in the Kenneth Dike library, university of Ibadan, Ibadan to find out the utilization pattern of the users and determin the effectiveness of the newspaper provision and services. Ninety six (96) library users were interviewed using questionnaire and direct interview methods. Participatory observation methods were also employed to get the information. The findings indicate that newspaper users in the library are facing some general problems. Adequate space needs to be provided for newspaper readers in acedemic libraries. Indexing of the newspapers will also help make information retrieval easier. It is recommended that library schools should provide courses that will deal with newspaper indexing, organization of newspaper collections, preservation and dissemination of newspaper information should be taught. A professional librarian, a library officer and a library attendent, for the effective provison of adequate newspaper information services, should man the newspaper section.